2022
DOI: 10.3390/molecules28010254
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Group VIII Elements into a 2D Rigid pc-C3N2 Monolayer to Achieve Single-Atom Catalysts with Excellent OER Activity: A DFT Theoretical Study

Abstract: Under DFT calculations, a systematic investigation is carried out to explore the structures and oxygen evolution reaction (OER) catalytic activities of a series of 2D single-atom catalyst (SAC) systems, which are constructed by doping the transition metal (TM) atoms in group VIII into the cavities of rigid phthalocyanine carbide (pc-C3N2). We can find that when Co, Rh, Ir and Ru atoms are doped in the small or large cavities of a pc-C3N2 monolayer, they can be used as high-activity centers of OER. All these fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…At last, we compare the HER/OER performances of our proposed electrocatalysts with those of other reported materials. In the cases of HER, monolayer MoSi 2 N 4 , Ni-doped β-Sb, Co–Mo 5 N 6 heterojunction, Ni-doped graphene, and AgPd alloys were considered as the excellent HER catalysts, and the corresponding |η HER | values are within 0.01–0.10 V, whose catalytic activities are similar to or even better than that of the Pt(111) surface (|η HER | = 0.09 eV) . In the cases of OER, it is found that the Rh-borophane, Rh-doped C 2 N, Ni-doped Mo 2 B 2 , Rh–N 4 –, and Ni/Pd–C 4 -doped graphene are promising candidates as OER catalysts, with the η OER values in the range of 0.31–0.53 V, which can compete with the most advanced IrO 2 (η OER = 0.56 V) and RuO 2 (η OER = 0.42 V) catalysts .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At last, we compare the HER/OER performances of our proposed electrocatalysts with those of other reported materials. In the cases of HER, monolayer MoSi 2 N 4 , Ni-doped β-Sb, Co–Mo 5 N 6 heterojunction, Ni-doped graphene, and AgPd alloys were considered as the excellent HER catalysts, and the corresponding |η HER | values are within 0.01–0.10 V, whose catalytic activities are similar to or even better than that of the Pt(111) surface (|η HER | = 0.09 eV) . In the cases of OER, it is found that the Rh-borophane, Rh-doped C 2 N, Ni-doped Mo 2 B 2 , Rh–N 4 –, and Ni/Pd–C 4 -doped graphene are promising candidates as OER catalysts, with the η OER values in the range of 0.31–0.53 V, which can compete with the most advanced IrO 2 (η OER = 0.56 V) and RuO 2 (η OER = 0.42 V) catalysts .…”
Section: Resultsmentioning
confidence: 99%
“…In the cases of HER, monolayer MoSi 2 N 4 , 63 Nidoped β-Sb, 64 Co−Mo 5 N 6 heterojunction, 65 Ni-doped graphene, 66 and AgPd alloys 54 were considered as the excellent HER catalysts, and the corresponding |η HER | values are within 0.01−0.10 V, whose catalytic activities are similar to or even better than that of the Pt(111) surface (|η HER | = 0.09 eV). 67 In the cases of OER, it is found that the Rh-borophane, 12 Rhdoped C 2 N, 68 Ni-doped Mo 2 B 2 , 69 Rh−N 4 −, and Ni/Pd−C 4doped graphene 11 are promising candidates as OER catalysts, with the η OER values in the range of 0.31−0.53 V, which can compete with the most advanced IrO 2 (η OER = 0.56 V) and RuO 2 (η OER = 0.42 V) catalysts. 2 In addition, some excellent bifunctional catalysts by combining HER and OER functions have been proposed, such as Ni-and Cu-doped MXenes, 13 Mn−Ni 3 S 2 , 70 and Ni-doped Mo 2 B 2 , 71 whose |η HER | and η OER values are within the range of 0.02−0.24 and 0.25−0.52 V, respectively.…”
Section: Her Performance Of Tm/c 3 Bmentioning
confidence: 99%
“…To describe the electronic structure of the material, using the PBE function and the k -point path of Figure d, we calculated the band structure of the p-C 2 N monolayer, as shown in Figure e. As we expected, the valence band maximum (VBM) and conduction band minimum (CBM) of p-C 2 N both cross the Fermi level similar to other PGCNs with porphyrin-like units, indicating metallic properties and suggesting high charge transfer capability. The relevant electronic density of states (DOS) and projected electronic density of states (PDOS) imply bonding types and strengths, as depicted in Figure f.…”
Section: Resultsmentioning
confidence: 73%
“…2(a)-(c)). 29,30 Similarly, the projected density of states (PDOS) of the three substrates indicated that the VCoS catalyst has the highest density of states near the Fermi level (Fig. 2(d)-(f)).…”
Section: Electrocatalytic Enhancement Mechanismmentioning
confidence: 87%